Extracellular vesicle-mediated communication in host-parasite interactions: insight from Fasciola hepatica - Torre-Escudero, Eduardo de la; Robinson, Mark W. (Annals of Translational Medicine; Vol 5, Supplement 1 (May 15, 2017): Annals of Translational Medicine, 2017)
In recent years, extracellular vesicles (EVs) have been accepted as a new intercellular communication system that mediate the transfer of proteins, lipids, mRNA, microRNA and other non-coding RNA species. Special attention has been paid to the role of EVs in the establishment and progression of human diseases. Indeed, perturbing EV production to modulate their pathological effects is an attractive therapeutic option that has been successful in a number of diseases, including cancer (1). To the same extent, several studies have described the contribution of parasite-derived EVs to the modulation of the host immune system (2-4) or the pathological effects on host cells (5). Tools such as transcriptomics and proteomics, have been particularly useful for identification of the immunomodulatory molecules that parasites package into EVs (6). A better understanding of how parasite EVs are produced and interact with host cells may open new avenues for parasite control, since the selective inhibition of these would prevent the delivery of potent immunomodulators that induce a host immune phenotype that favors parasite survival.